Places and Purposes of Popular Music Education Perspectives from the Field. - Powell, Bryan (Intellect Books, 2022)
Edited collection including contributions from scholars and popular music educators in response to the question "what are the place and purpose of popular music education?" The book aims to broaden and diversify the conversation and community around popular music education globally. 7 b&w illus.